Research Output and International Cooperation Among Countries During the COVID-19 Pandemic: Scientometric Analysis - Grammes, Nadja; Millenaar, Dominic; Fehlmann, Tobias; Kern, Fabian; Böhm, Michael; Mahfoud, Felix; Keller, Andreas (JMIR Publications, 2020)
BackgroundThe COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has instigated immediate and massive worldwide research efforts. Rapid publication of research data may be desirable but also carries the risk of quality loss. ObjectiveThis analysis aimed to correlate the severity of the COVID-19 outbreak with its related scientific output per country. MethodsAll articles related to the COVID-19 pandemic were retrieved from Web of Science and analyzed using the web application SciPE (science performance evaluation), allowing for large data scientometric analyses of the global geographical distribution of scientific output. ResultsA total of 7185 publications, including 2592 articles, 2091 editorial materials, 2528 early access papers, 1479 letters, 633 reviews, and other contributions were extracted. The top 3 countries involved in COVID-19 research were the United States, China, and Italy. The confirmed COVID-19 cases or deaths per region correlated with scientific research output. The United States was most active in terms of collaborative efforts, sharing a significant amount of manuscript authorships with the United Kingdom, China, and Italy. The United States was China's most frequent collaborative partner, followed by the United Kingdom. ConclusionsThe COVID-19 research landscape is rapidly developing and is driven by countries with a generally strong prepandemic research output but is also significantly affected by countries with a high prevalence of COVID-19 cases. Our findings indicate that the United States is leading international collaborative efforts.